Mental Disorders and Thrombotic Risk - Hoirisch-Clapauch, Silvia; Nardi, Antonio E.; Gris, Jean-Christophe; Brenner, Benjamin (Seminars in Thrombosis and Hemostasis, 2013)
Patients with psychosis, severe depression, or chronic stress are at increased risk for thromboembolism. Evidence suggests that tissue plasminogen activator (tPA) and plasminogen activator inhibitor-1 (PAI-1) imbalance may play an important role in pathophysiology of mental and thromboembolic disorders. tPA facilitates clot dissolution and participates in several brain functions, including response to stress, learning, and memory. Depression is characterized by high PAI-1 levels, and conditions related to a hypofibrinolytic status, such as polycystic ovary syndrome and metabolic syndrome, are associated with an increased risk for both depression and cardiovascular events. Depression/psychosis may occur when estrogen and progesterone levels decrease. Estrogen inhibits synthesis of transforming growth factor-β (TGF-β), a protein increasing PAI-1 synthesis, whereas progesterone induces brain-derived neurotrophic factor release, stimulating tPA expression in neurons. Synthetic progestogens (progestins) may cause severe depression. Notably, progestin metabolites, which may prevent synthesis of natural progesterone by feedback, do not cross the blood–brain barrier. Intense suprapubic menstrual cramp, which may relate to difficulty to dissolve clots, correlates with severe premenstrual tension. Exercise, which increases tPA synthesis, has antidepressive and antithrombotic effects. We suggest that thromboembolism and some mental disorders are mechanistically related: tPA–PAI-1 imbalance seems to be a common denominator.
Keywords: venous thromboembolism; depression; schizophrenia; psychosis; mental stress; PAI-1; plasminogen activator